Kebijakan Organisasi dan Produktivitas AI antara Teknologi dan Potensi Manusia di Dunia Kerja - Ignatius Wilson; Yosua Petrus Wijaya; Lea Putra Karuna (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) implementation on work productivity and the role of organizational policies in balancing technology integration and human potential development. A quantitative approach was used with a survey method targeting employees in various industrial sectors that have adopted AI technology. The data was analyzed using regression techniques to examine the relationship between variables such as organizational policy, human resource development, organizational culture, and human-AI collaboration on productivity. The results show that AI implementation has a significant effect on increasing work efficiency, but its effectiveness is greatly influenced by adaptive policies, adequate human resource training, and an organizational culture that is inclusive of innovation. This research contributes theoretically to the development of technology and human resource management, as well as providing practical benefits for organizations in designing policies that encourage optimal synergy between humans and technology.